2020
DOI: 10.1002/chem.202001978
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Boosted Rh‐Catalyzed Hydroaminomethylation Reaction: A Mechanistic Insight

Abstract: We report aR h-catalyzedh ydroaminomethylation reaction of terminal alkenes in glycerolt hat proceeds efficiently under mild conditions to produce the corresponding amines in relatively high selectivity towards linear amines, moderate to excellent yields by using al ow catalyst loading (1 mol %[ Rh],2mol %p hosphine) and relative low pressure (H 2 /CO, 1:1, total pressure 10 bar). This work sheds light on the importance of glycerol in enabling enamine reduction via hydrogen transfer.M oreover,e vidence for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…8,11,12 Therefore, various efforts have thus been devoted to the design of bi-functional catalytic systems. [20][21][22][23][24][25][26][27] By using 2-fluoro-4-methylbenzoic acid as a co-catalyst, Abolhasani and co-workers increased the reactivity of Rh/4,5-bis(diphenylphosphino)-9,9-dimethyl-xanthene by 70-fold in HAM. 20 Chen's group synthesized water-soluble diphosphine ligands and applied them in Rh-catalyzed HAM of vinylarenes using anilines in water with good branch selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,12 Therefore, various efforts have thus been devoted to the design of bi-functional catalytic systems. [20][21][22][23][24][25][26][27] By using 2-fluoro-4-methylbenzoic acid as a co-catalyst, Abolhasani and co-workers increased the reactivity of Rh/4,5-bis(diphenylphosphino)-9,9-dimethyl-xanthene by 70-fold in HAM. 20 Chen's group synthesized water-soluble diphosphine ligands and applied them in Rh-catalyzed HAM of vinylarenes using anilines in water with good branch selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…21 Despite these advances, various stoichiometric additives still have to be added to achieve satisfactory yields and regioselectivity. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In contrast, heterogeneous catalytic systems that are effective for HAM are still few in number, and those with industrial potential are even rarer. Poor selectivity (usually <80 : 20 for l/b) with limited substrate scope, limited reusability and decreasing activity in <5 reactions was generally observed with supported Rh and Ru nanoparticles (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This is a significant drawback that has limited the scope of HAM reactions to non-hindered amines 13 , 14 . Recent studies have demonstrated advances in the rate acceleration and substrate scope expansion of HAM reactions 15 , 16 . However, examples of HAM with sterically hindered amines are rare, and alternative complex routes are developed specifically for their alkylation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the further development of more efficient cobalt and rhodium catalysts and the introduction of phosphorus ligands, HAM has become a powerful method for the synthesis of amines. [4][5][6][7][8][9][10][11][12][13][14][15] As HAM is a tandem catalytic process in which various catalytic cycles occur simultaneously, the conditions can be good for one catalytic cycle and deleterious for the other. For this reason, care in the choice of appropriate conditions is critical for the successful reaction sequence.…”
Section: Introductionmentioning
confidence: 99%
“…However, selectivity for amines was low and the reaction required harsh conditions (T>300 °C and pressures up to 150 bar). Due to the further development of more efficient cobalt and rhodium catalysts and the introduction of phosphorus ligands, HAM has become a powerful method for the synthesis of amines [4–15] . As HAM is a tandem catalytic process in which various catalytic cycles occur simultaneously, the conditions can be good for one catalytic cycle and deleterious for the other.…”
Section: Introductionmentioning
confidence: 99%